Improving content delivery in low-resource networks: a case study of the African Internet Ecosystem - Phokeer, Amreesh Dev (Department of Computer Science, 2022)
The Internet is one of the most successful inventions of recent times. The COVID-19 pandemic has, once again, proven the importance of the Internet to society, and this has further demonstrated how critical it is to build networks that are resilient, accessible and inclusive. However, the Internet in many African countries is still limited by both technical and regulatory challenges. It is along these lines that this thesis proposes a series of studies, supported by empirical evidence, to better understand the challenges of content delivery in African networks. The thesis starts by providing an understanding how the Internet is being used and consumed by low-income mobile Internet users in South African townships. By means of a mixed-methods study, combining quantitative network measurements with qualitative survey data, the thesis provides some useful insights about Internet usage patterns and the underlying reasons for specific user behaviour with regards to mobile data management. The research revealed how Internet usage patterns of users in low-resource settings are restrained by the lack of access, availability of services and data cost.It also reinforced the concept of locality of interest and at the same time showing that the mainstream Internet services remain very popular. Next, the thesis investigates the impediments faced by African users to access local content and cloud-based services. This is achieved through a study on web content hosting, focusing specifically on African local news and public sector websites. It was found that 85% of local news websites are hosted outside their respective countries by foreign companies, mostly in Europe and in the US. This section revealed how a majority of Africa's local content is still hosted remotely and this has a major incident on the Quality of Experience (QoE) of users in Africa. Considering the set of challenges of content delivery in Africa, companies such as Facebook and Google have introduced alternative mechanisms to deliver content to the end-user - purportedly using bandwidth-friendly and cost-effective technologies. This thesis performs an in-depth Quality of Service (QoS) analysis of: (1) Free Basics, a “zero-rated” service from Facebook and (2) Accelerated Mobile Pages (AMP), a mobile optimisation technology by Google. The aim of both Free Basics and AMP is to reduce the cost of access and improve the QoE on mobile devices through different techniques - albeit with some caveats pertaining to net neutrality and data privacy. However, the thesis reveals that Free Basics services provide weaker network performance than their paid counterparts, which contributes to a disjointed user experience. On the other hand, Google AMP pages can reduce traditional page sizes by a factor of 8 and the results show that Page Load Time (PLT) on African networks can significantly be improved. However, both Free Basics and Google AMP introduce serious concerns with regards to net neutrality and data privacy. One way to minimise the effects of cross-continental path is to host the content as close as possible to the end-users. For this, there must exist a robust interconnection ecosystem between African networks. The thesis performs a deep-dive in both intra-country and inter-country connectivity in Africa, looking into both delays and network path by means of a longitudinal active measurement study. The latter exposes interesting topological characteristics of cross-border connectivity and provides evidence on the existence of circuitous routing and a lack of peering within African networks. The thesis reveals a series of “communities”, in which countries have built up low-delay interconnectivity, dispelling the myth that intra-delays in Africa are universally poor. Finally and taking into account the above, the thesis studies how the development of localised Internet infrastructure such as Internet Exchange Points (IXPs) and Data Centres (DCs) can help democratise access to local content. Using a simple multi-level maturity model, the thesis categorises the readiness of African countries to provide a localised Internet infrastructure. The thesis further explores the above hypothesis by estimating the effect of increasing the number of participants of an IXP on the local content activity of the country. The latter was achieved by using a fixed-effects econometric model and a positive correlation was found between the scale of an IXP and the local content activity. The thesis finally provides some key policy points on how to improve content delivery in African networks.